Pengaruh Pendapatan Asli Daerah dan Dana Perimbangan Terhadap Alokasi Belanja Modal dengan Budget Ratcheting Sebagai Variabel Moderasi: (Studi Pada Pemerintah Daerah Kabupaten dan Kota di Provinsi Bali) - Ni Luh Putu Dita Silviani; I Made Pradana Adiputra (Vokasi : Jurnal Riset Akuntansi, 2023)
This study aims to determine the effect of regional original income and balancing funds on the allocation of capital expenditure and to determine the effect of budget ratcheting in moderating the relationship of each independent variable to the allocation of capital expenditure in district/city regional governments in the Province of Bali. The type of data in this research uses secondary data in the form of regional government financial reports in the form of APBD and LRA with a span of 6 years (2016-2021). This study uses data analysis in the form of tiered linear regression. The results of this study indicate that regional original income and balance funds have a significant positive effect on capital expenditure allocation. Furthermore, budget ratcheting has moderation properties, strengthening the influence of PAD on the allocation of capital expenditures and the effect of balancing funds on the allocation of capital expenditures